2007
DOI: 10.1029/2006jb004345
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of growth and lateral propagation of the Kashi anticline, southwest Chinese Tian Shan

Abstract: [1] The Kashi anticline is a north vergent, asymmetric, doubly plunging detachment fold located in the SW Tian Shan foreland. We combine structural, magnetostratigraphic, and topographic data to define the fold's lateral propagation, surface uplift, and concomitant exhumation. Two new magnetostratigraphic sections indicate that the fold began growing at $1.4 Ma and by 1.07 Ma, deformation had propagated eastward $13 km at an average rate of $40 km/Myr. Subsequently, propagation rates increased at least twofold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(150 citation statements)
references
References 55 publications
3
147
0
Order By: Relevance
“…Four stages of tectonic deformation in the Atushi Basin in front of the SW Chinese Tian Shan at 20 ~ 25 Ma, ca.16.3 Ma, 4 ~ 13.5 Ma and after 4 Ma were constrained by magnetostratigraphic study, which lead to a total north south shortening of 10 -32 km (Heermance et al, 2008). The kinematic mechanism of the Atushi and Kashi folds were well constrained by Scharer et al (2004) and Chen et al (2007).…”
Section: Introductionmentioning
confidence: 96%
“…Four stages of tectonic deformation in the Atushi Basin in front of the SW Chinese Tian Shan at 20 ~ 25 Ma, ca.16.3 Ma, 4 ~ 13.5 Ma and after 4 Ma were constrained by magnetostratigraphic study, which lead to a total north south shortening of 10 -32 km (Heermance et al, 2008). The kinematic mechanism of the Atushi and Kashi folds were well constrained by Scharer et al (2004) and Chen et al (2007).…”
Section: Introductionmentioning
confidence: 96%
“…For example, using in situ cosmogenic 10 Be measurements in quartzites, Jackson et al [28] obtained average uplift and propagation rates of 0.10-0.15 m/ka and 1.0-2.0 m/ka, respectively, over the last 450 ka for a Late Quaternary anticline forming above a blind reverse fault in Central Otago, New Zealand, whereas Chen et al [24,65] reported shortening rates of 2.0-4.4 m/ka and lateral propagation rates of c. 15-40 m/ka from the Chinese Tien Shan.…”
Section: Rates Of Displacement and Lateral Propagationmentioning
confidence: 99%
“…Of specific interest here, the geomorphic expression of active fault-related fold structures provides a potential opportunity to decipher both fold kinematics and mechanisms of lateral growth, although data from natural examples is not abundant [4,6,15,19,23,24]. Recently, the geometry of drainage basins and river networks (including stream profile analysis) has been used to interpret the spatial and temporal evolution of fault-related structures in both extensional [25][26][27] and contractional settings [10,18,23,[28][29][30][31][32] due to the strong control that fault-or fold-related uplift has on drainage basin development, stream initiation and diversion.…”
Section: Introductionmentioning
confidence: 99%
“…Fault plane solutions of earthquakes consistently show reverse or thrust faulting. Evidence of active faulting is widespread (Abdrakhmatov et al, 2007;Chedia, 1986;Laverov and Makarov, 2005), and rates of slip on several faults exceed 1 mm yr -1 (Chen et al, 2007;Thompson et al, 2002).…”
Section: Geologic Backgroundmentioning
confidence: 99%